Effects of financial leverage on stock returns in Bursa Malaysia - Lau, Wei Theng (2016)
Motivated by the over-leveraging problem widely claimed to have triggered the recent global financial crisis, this thesis aims to provide empirical evidence to three major issues of financial leverage: the role of cash flow, the existence of the leverage threshold,and the role of leverage maturity. Employing data relating to about 500 firms from 1986-2012, the sector-specific results suggest that industry, cash flow, debt maturity, nonlinearity,as well as different leverage measures are among the important factors that could affect the leverage-to-stock returns nexus.As cash flows exhibit important implications based on different capital structure theories,the first objective of the study is to examine the role of cash flows in affecting leveraged stock returns. The panel regressions show that industry-specific analysis matters due to the various marginal effects of leverage conditional on cash flows across sectors. Cash flow from operating activities, cash flow for capital expenditure, and free cash flow are employed and each exhibits an important role in affecting the leverage-to-returns nexus in most of the sectors. Findings are robust to market and book measures of leverage, net or inclusive of cash position. The conditional leverage impacts remain robust to firm effects and time effects in handling the firm-level financial data.The second objective of this thesis is motivated by both the proposed over-leverage issue in the financial markets nowadays as well as the arguments of trade-off theory. Panel threshold regressions show that various financial leverage thresholds are identified in relation to stock returns with their impacts differing across sectors. Apart from 3 out of 12 sectors which do not show the existence of a threshold, the empirical results reveal that financial leverage contributes negatively to stock returns, or the positive impact decreases when leverage rises further. As such, excessive financial leverage should be avoided in maximising shareholders’ wealth. The empirical results are robust using two indicators of financial leverage as well as in different sample periods.The third objective of this study is to examine whether the effects of financial leverage on returns can be explained by debt maturity, especially as maturity mismatch problems have been widely discussed since the last Asian financial crisis. When the financial leverage is divided into short-term debt and long-term debt, a total of 9 sectors reveal that either form of leverage has a significant relationship with stock returns. The empirical findings also suggest that the claim that short-term debt carries a higher risk,therefore investors are compensated with higher returns is rebuttable. The findings are confirmed by using book leverage and market leverage, including various adjusted standard errors to accommodate the characteristics of firm-level financial data.